Assessment of existing infrastructure and environmental planning of industrial parks in Dasmarinas, Cavite and its implications to social, economic, and institutional plans of local government unit. - Sacdalan, John Cristopher D., II; Liwag, Carmelita R.E.U (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman., 2022)
The role of industrial parks in economic development is paramount to the nation’s advancement as they create a competitive standpoint. They can contribute to the flourishment of urban areas but along with such success are concerns that impact society. Factories and manufacturing companies inside these parks can affect the condition of the environment. Despite the provision of existing laws and building codes being set in place, to a certain extent, the implementation process can be compromised operationally by the industrial park management. In addition, the implementation guidelines are only revisited when environmental catastrophes strike. This study developed a standardized tool containing criteria that captured the infrastructure planning and environmental compliance features of two (2) target industrial parks. These criteria provided a systematic scoring process that determined the empirical basis of the existing operational conditions of industrial parks. This assessment tool was found to be effective and viable in assessing and comparing the gaps between actual versus standard conditions. Results showed significant discrepancies, thereby underscoring the need to carry through effective ways to increase compliance and performance to ensure sustainable of urban development.
Thesis (M.A. Urban and Regional Planning)--University of the Philippines
Keywords: Industrial districts -- Philippines -- Dasmarinas (Cavite).; Infrastructure(Economic) -- Philippines -- Dasmarinas (Cavite).; Environmental protection -- Planning -- Philippines -- Dasmarinas (Cavite).